Sufficient conditions of stochastic dominance for general transformations and its application in option strategy - Jianwei Gao; Feng Zhao (Kiel Institute for the World Economy (IfW), 2017)
A counterexample is presented to show that the sufficient condition for one transformation dominating another by the second degree stochastic dominance, proposed by Theorem 5 of Levy (Stochastic dominance and expected utility: Survey and analysis, 1992), does not hold. Then, by restricting the monotone property of the dominating transformation, a revised exact sufficient condition for one transformation dominating another is given. Next, the stochastic dominance criteria, proposed by Meyer (Stochastic Dominance and transformations of random variables, 1989) and developed by Levy (Stochastic dominance and expected utility: Survey and analysis, 1992), are extended to the most general transformations. Moreover, such criteria are further generalized to transformations on discrete random variables. Finally, the authors employ this method to analyze the transformations resulting from holding a stock with the corresponding call option.
Keywords: C51; D81; G1; 330; stochastic dominance; transformation; utility theory; option strategy